Is Usage of Visual Images in Online Marketing Effective? - Leung , Chi Hong (Asian Journal of Empirical Research, 2019)
This paper discusses the importance of visual images in online marketing communication such as on Facebook. Because of noise in online communication channels it is becoming more and more difficult for marketing messages to be noticed. Visual images are now common on social media and can attract target audience and consumers and draw their attention in the online environment. This paper presents a study that selected 37 companies’ photos posted on Facebook. Four of these companies were highlighted owing to the high popularity and acceptance of their photos. Qualitative research was performed to investigate what kinds of photos these companies posted from Feb 2018 to Jan 2019. The results of this study show that there are diverse types of photos (of food, children, sports, animals, landscape, automobile, portraits, architecture, macros, quotes, events, aerial, street, and documentary) used for various marketing purposes. We concluded that visual images are effective in online marketing.